Rozwiąż nierówności :
a)4x>5(x+1)
b)2(x-1)<3(x+1)-x
c)3(x+2)-2(3-x)≥8
d)2(3x-5)+10>3(2x-1)
e)5(2x+3)≤2(x+6)+15
f)10(x-2)-3(x+2)≥7x-20
g)7(x-1)-3(2x+3)≤2(x+2)-22
h)x(x+7)+14≥x²+7(x+2)
i)12(x-0,5)>6(2x+1)+5
j)18(x+1)-10(0,5x+2)>-5x-2

3

Odpowiedzi

2010-03-26T16:59:01+01:00
A) 4x>5(x+1)
4x>5x+5
4x-5x>5
-x>5
x<-5

b)2(x-1)<3(x+1)-x
2x-2<3x+1-x
2x-2x<1+2
0<3
nierówność sprzeczna
c)3(x+2)-2(3-x)≥8
3x+6-6+x≥8
4x≥8
x≥2

d)2(3x-5)+10>3(2x-1)
6x-10+10>6x-3
6x-6x>-3
0>-3
nierówność sprzeczna

e)5(2x+3)≤2(x+6)+15
10x+15≤2x+12+15
8x≤12
x≤1,5

f)10(x-2)-3(x+2)≥7x-20
10x-20-3x-6≥7x-20
0x≥0
nierówność tożsamościowa

g)7(x-1)-3(2x+3)≤2(x+2)-22
7x-7-6x-9≤2x+4-22
-x≤-18+7+9
-x≤-2
x≥2

h)x(x+7)+14≥x²+7(x+2)
x²+7x+14≥x²+7x+14
0≥0
nierówność tożsamościowa

i)12(x-0,5)>6(2x+1)+5
12x-6>12x+6+4
0x>16
nierówność sprzeczna

j)18(x+1)-10(0,5x+2)>-5x-2
18x+18-5-20>-5x-2
23x>-21
x>²¹₂₃
2010-03-26T16:59:01+01:00
A)4x>5(x+1)
4x>5x+5
4x-5x>5
-x>5 /:(-1)
x<-5

b)2(x-1)<3(x+1)-x
2x-2<3x+3-x
2x-3x+x<3+2
0<5

c)3(x+2)-2(3-x)≥8
3x+6-6+2x≥8
5x≥8 /:5
x≥1 ⅗

d)2(3x-5)+10>3(2x-1)
6x-10+10>6x-3
6x-6x>-3
0>-3

e)5(2x+3)≤2(x+6)+15
10x+15≤2x+12+15
10x-2x≤12+15-15
8x≤10 /:8
x≤1 ⅕

f)10(x-2)-3(x+2)≥7x-20
10x-10-3x-6≥7x-20
7x-7x≥-20+10+6
0≥-4

g)7(x-1)-3(2x+3)≤2(x+2)-22
7x-7-6x-9≤2x+4-22
x-2x≤-18+7+9
-x≤-2 /:(-1)
x≥2

h)x(x+7)+14≥x²+7(x+2)
x²+7x+14≥x²+7x+14
0≥0

i)12(x-0,5)>6(2x+1)+5
12x-6>12x+6+5
12x-12x>11+6
0>17
nierówność sprzeczna

j)18(x+1)-10(0,5x+2)>-5x-2
18x+18-5x-2>-5-2
13x>-7-16
13x>-23 / :13
x>-23/13

2010-03-26T17:14:55+01:00
A) 4x>5(x+1)
4x>5x+5
4x-5x>5
-x>5 /*(-1)
x<-5
b) 2(x-1)<3(x+1)-x
2x-2<3x+3-x
2x-3x+x<3+2
0<5
nierówność sprzeczna
c) 3(x+2)-2(3-x)≥8
3x+6-6+2x≥8
5x≥8 /5
x≥⁸/₅
d)2(3x-5)+10>3(2x-1)
6x-10+10>6x-3
0>-3
nierówność sprzeczna
e)5(2x+3)≤2(x+6)+15
10x+15≤2x+12+15
10x-2x≤27-15
8x≤12
x≤¹²/₈
f)10(x-2)-3(x+2)≥7x-20
10x-20-3x-6≥7x-20
0≥6
nierówność sprzeczna
g)7(x-1)-3(2x+3)≤2(x+2)-22
7x-7-6x-9≤2x+4-22
x-2x≤-18+16
-x≤-2
x≥2
h)x(x+7)+14≥x²+7(x+2)
x²+7x+14≥x²+7x+14
0≥0
i)12(x-0,5)>6(2x+1)+5
12x-6>12x+6+5
0>17
nierówność sprzeczna
j)18(x+1)-10(0,5x+2)>-5x-2
18x+18-5x-20>-5x-2
18x>0
x>0